1998
DOI: 10.1099/00221287-144-9-2629
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine biosynthesis and the utilization of succinate and glutamine by Rhizobium etli and Sinorhizobium meliloti

Abstract: Sinorhizobium meliloti 1021 and Rhizobium etli CE3 turn over nitrogen and carbon from glutamine to ammonium and CO2, respectively. Some of the ammonium released is assimilated back into glutamine, indicating that a glutamine cycle similar to that in Neurospora operates in Rhizobium. In addition, a previously unrecognized metabolic pathway in Rhizobium was discovered - namely, conversion of glutamine-carbon to γ-hydroxybutyric acid and β-hydroxybutyric acid. Additionally, some of the 2-oxoglutarate derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Amino acid utilization requires active uptake, deamination/deamidation, common metabolic pathways, such as the citric acid cycle and gluconeogenesis, and NH 4 ϩ excretion. R. etli mutants showing very low levels of glutaminase, asparaginase, and aspartase activity are Nod ϩ /Fix ϩ (46,47,50,79). Enzymes involved in gluconeogenesis are expressed in BTs of R. leguminosarum, S. meliloti, and Rhizobium sp.…”
Section: Nhmentioning
confidence: 99%
“…Amino acid utilization requires active uptake, deamination/deamidation, common metabolic pathways, such as the citric acid cycle and gluconeogenesis, and NH 4 ϩ excretion. R. etli mutants showing very low levels of glutaminase, asparaginase, and aspartase activity are Nod ϩ /Fix ϩ (46,47,50,79). Enzymes involved in gluconeogenesis are expressed in BTs of R. leguminosarum, S. meliloti, and Rhizobium sp.…”
Section: Nhmentioning
confidence: 99%
“…The nonessential amino acid L-glutamine (Gln) is the most abundant amino acid in plasma (13) and is an energy substrate for most cells (14,15). Extensive research in animal models of endotoxin shock, including severe injury models, has demonstrated that supplementation with Gln improves survival, enhances immune and gut barrier function, decreases bacteremia, and inhibits gut mucosal atrophy (16,17).…”
mentioning
confidence: 99%
“…T he nonessential amino acid L-glutamine (Gln) 4 is the most abundant amino acid in plasma (1), and Gln is an energy substrate for most cells (2,3). Consequently, Gln plays an important role in nitrogen and carbon-skeleton exchange among different tissues, where this amino acid fulfills many different physiological functions (4).…”
mentioning
confidence: 99%